FOSTERING STUDENTS’ ENGAGEMENT IN SYNCHRONOUS LEARNING USING INTERACTIVE WEB-BASED MEDIA - Nia Kurniawati; Fuzi Fauziyah (Indonesian EFL Journal, 2022)
This research was conducted to investigate the implementation of BookWidgets to facilitate the students’ engagement in synchronous learning through web-conferencing. The subject were students of Al-Madina Vocational High School from 11 OTKP, which involved 29 students. The objective of this implementation was to foster the students’ engagement during synchronous class, to find out the way BookWidgets facilitated the students’ engagement, and to reveal the most dominant students’ engagement types when BookWidgets was integrated. This study was a nested mix-method, employing observation, interview, and survey to gather the qualitative and quantitative data. It was applied for four meetings. The result of this research showed that this implementation could engaged students behaviorally, emotionally, and cognitively. They presented positive behaviors, involvement, effort, positive emotion, achievement, and good self-regulation during their learning. The interesting features had created meaningful learning for students in terms of verbal participation, students’ feeling and students’ academic investment. The easy use features of BookWidgets made students enthusiastic and reduced the boredom which made them motivate and engage in following the synchronous learning. Based on the statistical data, BookWidgets facilitated behavioral engagement with 78%, emotional engagement with 76%, and cognitive engagement with 75%. From this result, it could be seen that BookWigets mostly facilitated the behavioral engagement. Two or more engagement types were possible to occur simultaneously, but the level of each engagement could be different.Keywords: students’ engagement; synchronous learning; BookWidgets.